Neutronic and Thermal-Hydraulic Safety Analysis for the Optimization of the Uranium Foil Target in the RSG-GAS Reactor - S. Pinem; T.M. Sembiring; P.H. Liem (Atom Indonesia, 2016)
The G. A. Siwabessy Multipurpose Reactor (Reaktor Serba Guna G.A. Siwabessy, RSG-GAS) has an average thermal neutron flux of 2×1014 neutron/(cm2 sec) at the nominal power of 30 MW. With such a high thermal neutron flux, the reactor is suitable for the production of Mo-99 which is widely used as a medical diagnostic radioisotope. This paper describes a safety analysis to determine the optimum LEU foil target by using a coupled neutronic and thermal-hydraulic code, MTR-DYN. The code has been developed based on the three-dimensional multigroup neutron diffusion theory. The best estimated results can be achieved by using a coupled neutronic and thermal-hydraulic code. The calculation results show that the optimum LEU foil target is 54 g corresponding to the reactivity change of less than the limit value of 500 pcm. From the safety analysis for the case when the primary flow rate decreased by 15% from its nominal value, it was found that the peak temperatures of the coolant and cladding are 69.5°C and 127.9°C, respectively. It can be concluded that the optimum LEU foil target can be irradiated safely without exceeding the limit value.Received: 10 December 2015; Revised: 2 August 2016; Accepted: 4 August 2016